The Effects of Medicaid Expansion on Job Loss Induced Mental Distress during the COVID-19 Pandemic in the US - Sankar Mukhopadhyay (Institute of Labor Economics (IZA), 2022)
The COVID-19 pandemic led to an unprecedented level of job losses in the U.S., where a job loss is also associated with the loss of health insurance. This paper uses data from the 2020 Household Pulse Survey (HPS) and difference-in-difference (DD) regressions to estimate the effect of the Medicaid expansion on anxiety and depression associated with job loss. Estimates show that the respondents who live in expansion states are 96.6% (36.3%) more likely to have Medicaid coverage, and correspondingly, 14.2% (7.6%) less likely to have moderate to severe mental distress following their job loss (a family member's job loss) compared to those living in non-expansion states. Further explorations suggest that the economic security provided by Medicaid is as important (if not more) as the access or utilization to healthcare. The difference-in-difference-in-difference (DDD) estimates using just above and below the Medicare eligibility age (65) confirm these results.
Keywords: I12; I18; J6; 330; job loss; depression; anxiety; mental health; COVID-19; Medicaid